Cost effectiveness of Alternative Helicobacter pylori Eradication Strategies in the Management of Duodenal Ulcer. (1st June 1997) - O'Brien, Bernie; Goeree, Ron; Hunt, Richard; Wilkinson, Joanne; Levine, Mitchell; William, Andrew
Abstract : Published data and techniques for decision analysis were used to construct a model to estimate the cost effectiveness of nine alternative strategies for the management of patients diagnosed with uncomplicated duodenal ulcer. Two strategies of intermittent therapy with either ranitidine or omeprazole, one strategy of continuous maintenance treatment with ranitidine, and six strategies for ulcer healing and eradication of Helicobacter pylori infection were considered. Healing time curves were estimated by using published data, allowing for estimation of expected time for acute healing episodes. The expected number of weeks to heal per patient, in a one-year period, was estimated by combining healing time data with probability of ulcer recurrence. It was found that patients that underwent any of the six H pylori eradication regimens had fewer days with ulcer per year than those who underwent maintenance or intermittent ranitidine. Four eradication regimens had lower costs and better outcomes than ranitidine therapy. In comparing H pylori strategies, the two strategies of omeprazole plus one antibiotic (either amoxicillin or clarithromycin) are more costly than omeprazole plus two antibiotics (specifically amoxicillin and metronidazole or clarithromycin and metronidazole) and result in similar outcomes. Although omeprazole-based eradication regimens are more costly than ranitidine bismuth triple therapy, they are associated with fewer recurrences of ulcer and days of symptoms. A limitation of the analysis is that it did not incorporate issues of compliance and metronidazole resistance; however, the former concern may be less of an issue as H pylori regimens become simpler and shorter in duration.